(untitled) (Revista Inclusiones, 2020)
Amid the global fight against the pandemic and economic instability, extreme factors come to affect the life and health of people, which pose a serious threat for the population in Russia and abroad. The paper addresses the specifics of the implemented measures to safeguard food security in Russia amid the global fight against the COVID-19 pandemic. The author believes that the coronavirus will switch the focus of most countries inwards and keep it within their borders rather than abroad, at least for several years. Accordingly, many countries, including Russia, risk being dragged into a looming food crisis, unless measures are taken to support food supply chains between countries; to ensure healthcare and medicine provision and social protection of the underprivileged; to mitigate the consequences of the pandemic for the food system as a whole. The recommendations are to revise the list of socially important food products and to curtail price growth for the respective items, as well as to stockpile strategic food reserves as prioritised for economic accessibility for the population. All these and other measures should lay the foundation of sustainable demographic development aligned with public health policies aimed at the native Russian population. The conducted analysis specifically involved qualitative and quantitative methodological studies based on the comparative analysis of food supply performance amid the COVID-19 pandemic and economic instability. The present study provides references to foreign practices of implementing emergency measures to ensure social protection of the population. Proposals are drawn on how to safeguard food security in Russia.